MORAL VALUES IN ENGLISH TEXTBOOK: “WHEN ENGLISH RINGS A BELL” - Sherina Kusramadhani; Rahmadi Nirwanto; Hesty Widiastuty (PROJECT (Professional Journal of English Education), 2022)
This research was aimed to know about moral values in the textbook. Textbooks were analyzed by using critical discourse analysis (CDA) data was obtained through analyzing the whole texts. This study attempts to examined the moral values which appeared in the English textbook "When English Rings a Bell" for seventh of Junior high school or equivalent based on the curriculum and presidential decree to teach character education to students, which included 18 moral values and to describe the moral values represented in the practice of conversational texts. It was designed as content analysis in the form of descriptive qualitative research. The result of this study were (1) The most apparently of moral values found in the English textbook were social awareness, curiosity, and responsibility, and (2) Moral values in English textbook was found in the conversation text through implicitly in the form of a moral message conveyed by the writer. it can be concluded that the authors of this textbook focus more on social values such as social awareness, curiosity, responsibility in the form of teaching moral values as character education for students at an early age. Then, the textbook was contained the moral values based on the presidential decree about character education. The textbook was quite good, but it can be improved. Keywords:  Moral Value, English Textbook, Critical Discourse Analysis